VD_FINDINFO Décision / 2013 / 456 vom 15. Mai 2013 - VD Tribunal cantonal (2013)
DÉTENTION PRÉVENTIVE, RISQUE DE COLLUSION, RISQUE DE RÉCIDIVE | 221 al. 1 let. b CPP (CH), 221 al. 1 let. c CPP (CH), 226 al. 5 CPP (CH), 237 CPP (CH), 393 al. 1 let. c CPP (CH)